Improving Participation and Quality of Village Development Planning: Study in Sigaluh Village, Banjarnegara Regency - Astuti, Margi; Mazid, Sukron; Wulansari, Atsani; Farikah; Hasanah, Imroatun (ASANKA : Journal of Social Science and Education, 2024)
This study aims to evaluate the quality of village development planning in Sigaluh Village, Sigaluh District, Banjarnegara Regency, based on Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration (Permendes) Number 21 of 2020. This study used qualitative descriptive methods with primary and secondary data obtained through purposive sampling. Data collection techniques are done through observation, in-depth interviews, and documentation. Data analysis involves data reduction, data presentation, verification, and conclusion. Data validity was checked using source triangulation. The results showed that, first, village development planning efforts in Sigaluh Village had tried to involve community aspirations and participation. Second, several factors cause planning not to be fully in accordance with Permendes Number 21 of 2020, such as potential problems and suboptimal support and cooperation. The impact of this study shows that development planning in Sigaluh Village needs to be improved to be more in accordance with Permendes Number 21 of 2020 by improving community involvement and optimizing existing potential, support, and cooperation.